1978
DOI: 10.1115/1.3424274
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Strain Rate History and Temperature Effects During the Plastic Deformation of Close-Packed Metals

Abstract: A study is presented on the influence of strain rate and strain rate history on the flow stress of several metals. Experiments were performed on specimens of four polycrystalline metals: 1100-0 aluminum, OFHC copper, AZ31 B magnesium, and commercially pure zinc. The experiments involve, the use of a modified Kolsky bar to increase abruptly the imposed strain rate, initially 2 × 10−4 s−1, by a factor of more than 106. Tests were performed at selected temperatures in the range T ≤ (1/2)Tm. The results include co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…In nearly al l cases , the stress-strain curve following the strain rate increment quickly joins the all-d ynamic curve, implying no "memory" effect in sharp contrast to the results of Senseny et al [13] for fcc and hcp metals , who found that the stress after the increment in strain rate was significantly lower than the all-d ynamic flow stress and approached it only graduall y with further straining. Thus , it appears that strain rate history has significantly less effect on flow stress in low carbon HRS , a bcc me ta l , than in aluminum or copper , fc c me ta l s , or magnesium or zinc , which ar e hcp metals [13]. One should note also the contrasting bahvior , as for upper and lower yield points , with the results of Frant : and Duffy [161 .…”
Section: -contrasting
confidence: 42%
“…In nearly al l cases , the stress-strain curve following the strain rate increment quickly joins the all-d ynamic curve, implying no "memory" effect in sharp contrast to the results of Senseny et al [13] for fcc and hcp metals , who found that the stress after the increment in strain rate was significantly lower than the all-d ynamic flow stress and approached it only graduall y with further straining. Thus , it appears that strain rate history has significantly less effect on flow stress in low carbon HRS , a bcc me ta l , than in aluminum or copper , fc c me ta l s , or magnesium or zinc , which ar e hcp metals [13]. One should note also the contrasting bahvior , as for upper and lower yield points , with the results of Frant : and Duffy [161 .…”
Section: -contrasting
confidence: 42%
“…We noted that the strain rate dependence of the deviation from the C-S law was consistent with the concept of a "recovery strain" contribution due to dynamic recovery, but that the addition of a second, shorter-range obstacle could also lead to the observed behavior. Fortunately, to a first approximation, these deviations can be ignored; but the detailed g, (8) variation should be incorporated into the model, either with tabular or empirical formats, for the best predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Existing experimental evidence indicates that the flow strength remains relatively high and strongly rate dependent under these conditions. 10,11,15,16 Figure 2 summarizes the variation of flow stress with shear strain rate for copper over a wide range of strain rates. The prediction of Eq.…”
Section: ͑2͒mentioning
confidence: 99%